2018
DOI: 10.1093/cercor/bhy183
|View full text |Cite
|
Sign up to set email alerts
|

Domain-Specific Diaschisis: Lesions to Parietal Action Areas Modulate Neural Responses to Tools in the Ventral Stream

Abstract: Neural responses to small manipulable objects ("tools") in high-level visual areas in ventral temporal cortex (VTC) provide an opportunity to test how anatomically remote regions modulate ventral stream processing in a domain-specific manner. Prior patient studies indicate that grasp-relevant information can be computed about objects by dorsal stream structures independently of processing in VTC. Prior functional neuroimaging studies indicate privileged functional connectivity between regions of VTC exhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 112 publications
(141 reference statements)
7
25
0
Order By: Relevance
“…One prominent view proposed by Gallivan and Culham () suggests that the ventral visual pathway may receive the outputs of visuomotor processes in frontal–parietal circuits prior to the onset of action (i.e., during the planning phase) to serve as a prediction mechanism of to‐be performed actions. Consistent with this possibility, a recent lesion‐activity mapping fMRI study in preoperative neurosurgery patients found that lesions involving the left SMG and adjacent voxels in the left anterior IPS were associated with reduced BOLD contrast for tools in the left medial fusiform gyrus, indicating that lesions to parietal action areas, including the left SMG, disrupt processing in the ventral visual pathway (Garcea et al, in press). Although speculative, in the tool transport condition the left SMG may query ventral stream representations of surface texture, as participants were instructed to imagine grasping the tool to move or transport it; in contrast, tool use epochs emphasize action kinematics and relative positioning of joint angles for accurate tool use, which may not emphasize to the same extent the processing of an object's material properties, including surface texture.…”
Section: Discussionmentioning
confidence: 84%
“…One prominent view proposed by Gallivan and Culham () suggests that the ventral visual pathway may receive the outputs of visuomotor processes in frontal–parietal circuits prior to the onset of action (i.e., during the planning phase) to serve as a prediction mechanism of to‐be performed actions. Consistent with this possibility, a recent lesion‐activity mapping fMRI study in preoperative neurosurgery patients found that lesions involving the left SMG and adjacent voxels in the left anterior IPS were associated with reduced BOLD contrast for tools in the left medial fusiform gyrus, indicating that lesions to parietal action areas, including the left SMG, disrupt processing in the ventral visual pathway (Garcea et al, in press). Although speculative, in the tool transport condition the left SMG may query ventral stream representations of surface texture, as participants were instructed to imagine grasping the tool to move or transport it; in contrast, tool use epochs emphasize action kinematics and relative positioning of joint angles for accurate tool use, which may not emphasize to the same extent the processing of an object's material properties, including surface texture.…”
Section: Discussionmentioning
confidence: 84%
“…Converging with this view are insights from the neurobiological phenomenon of diaschisis, whereby focal brain lesions affect neural processing in anatomically remote and physiologically intact regions (Carrera & Tononi, 2014;Garcea et al, 2018;Price, Warburton, Moore, Frackowiak, & Friston, 2001). Moreover, these data may provide a neural substrate for top-down attentional modulation effects (e.g., Reynolds & Chelazzi, 2004;Zhang & Kay, 2018) on occipital and temporal cortex, whereby responses are enhanced in tandem with attentional deployment and task demands.…”
Section: Discussionmentioning
confidence: 96%
“…2015 ; Garcea et al. 2018 ), and recent lesion evidence suggests that inferior parietal-to-medial fusiform connectivity disruption predicts abnormal tool processing ( Garcea, Almeida, et al. 2019 ) and tool use gesturing ability ( Watson et al.…”
Section: Discussionmentioning
confidence: 99%
“…2019 ). Moreover, in preoperative neurosurgery participants, the degree of reduced BOLD contrast for tools in the left medial fusiform gyrus was associated with lesions in the left inferior parietal lobule ( Garcea, Almeida, et al. 2019 ), suggesting that parietal lesions disrupt the processing of tools in functionally connected nodes in ventral temporal cortex.…”
Section: Introductionmentioning
confidence: 99%